Intraventricular Administration of Exosomes from Patients with Amyotrophic Lateral Sclerosis Provokes Motor Neuron Disease in Mice - Stavrovskaya, A V; Voronkov, D N; Pavlova, A K; Olshanskiy, A S; Belugin, B V; Ivanova, M V; Zakharova, M N; Illarioshkin, S N (Actanaturae, 2024)
Amyotrophic lateral sclerosis (ALS) is a severe disease of the central nervous system (CNS) characterized by motor neuron damage leading to death from respiratory failure. The neurodegenerative process in ALS is characterized by an accumulation of aberrant proteins (TDP-43, SOD1, etc.) in CNS cells. The trans-synaptic transmission of these proteins via exosomes may be one of the mechanisms through which the pathology progresses. The aim of this work was to study the effect of an intraventricular injection of exosomes obtained from the cerebrospinal fluid (CSF) of ALS patients on the motor activity and CNS pathomorphology of mice. The exosomes were obtained from two ALS patients and a healthy donor. Exosome suspensions at high and low concentrations were injected into the lateral brain ventricles of male BALB/c mice ( = 45). Motor activity and physiological parameters were evaluated twice a month; morphological examination of the spinal cord was performed 14 months after the start of the experiment. Nine months after administration of exosomes from the ALS patients, the animals started exhibiting a pathological motor phenotype; i.e., altered locomotion with paresis of hind limbs, coordination impairment, and increasing episodes of immobility. The motor symptoms accelerated after administration of a higher concentration of exosomes. The experimental group showed a significant decrease in motor neuron density in the ventral horns of the spinal cord, a significant increase in the number of microglial cells, and microglia activation. The TDP43 protein in the control animals was localized in the nuclei of motor neurons. TDP43 mislocation with its accumulation in the cytoplasm was observed in the experimental group. Thus, the triggering effect of the exosomal proteins derived from the CSF of ALS patients in the development of a motor neuron pathology in the experimental animals was established. This confirms the pathogenetic role of exosomes in neurodegenerative progression and makes it possible to identify a new target for ALS therapy.